Ruumiinosannimien kieliopillistumisesta suomessa ja virossa: tarkust ei wõi käega külge panna - Ojutkangas, Krista (Virittäjä, 2000)
Grammaticalization of body-part nouns in Finnish and Estonian (englanti) 1/2000 (104) Krista Ojutkangas (University of Turku; krioju@utu.fi) GRAMMATICALIZATION OF BODY-PART NOUNS IN FINNISH AND ESTONIAN Grammaticalization refers to a continuous process of change in a language whereby a lexical unit develops into a grammatical one: a word originally with a concrete referent becomes an indicator of a grammatical relationship. Two principal conceptualization models can be used to describe the grammaticalization of body-part nouns. The anthropomorphic model is based on the human body, with spatial concepts being expressed in the language using body-part nouns. The salience of the actions of the front part of the body, the face, arms and hands, and the notion of a ’front-rear’ axis, underlie this conceptualization. Spatial concepts can, alternatively, be based on the anatomy of four-legged (domesticated) animals; this is the zoomorphic conceptualization model. This article focuses on the grammaticalization of Finnish and Estonian postpositions and adverbs developed from body-part nouns and expressing ’beside’ or ’next to’. The roots of the grammatical units examined are kuve (Finn.) ’loin, flank’, kylki (Finn.) klg (Est.) ’side, flank’, korva (Finn.) krv (Est.) ’ear’ and rinta (Finn.) ’chest, breast’. The writer asserts that the grammaticalization of these words is based primarily on the zoomorphic conceptualization model, but with certain qualifications. Firstly, use of the zoomorphic model also incorporates anthropocentric features: central to the grammaticalization of words referring to the side parts of the body is the orientation of the speaker’s observation or action which is directed towards the side parts of the animal. The salience of the side parts arises from the observation made by the speaker. Secondly, clear features of the anthropomorphic model can also be observed in the grammaticalization of the Finnish word rinta. The postpositions and adverbs examined can all be used to express location in concrete or abstract space. Concrete space refers to a location in contact with, next to, close to or in connection with something; common to these expressions is metonymy, the transfer of meaning from ’the part’ to ’the space surrounding the part’. Abstract spaces include the world of politics or narrative, and the development of these expressions is based on the metaphorical extension of concrete spatial meanings. Chronological proximity, affiliation and comparison are extensions of basic abstract spaces and are linked with each other: location in space presumes a location in time, and entities functioning together simultaneously can be compared with each other. Kielenainekset kõrv (kieli: viro, sivulla: 3) korva (kieli: suomi, sivulla: 2) kuve (kieli: suomi, sivulla: 2) külg (kieli: viro, sivulla: 3) kylki (kieli: suomi, sivulla: 2) rind (kieli: viro, sivulla: 3) rinta (kieli: suomi, sivulla: 2) selg (kieli: viro, sivulla: 6) selkä (kieli: suomi, sivulla: 4)